Karakteristik Graf Dengan Sisi Bilangan Fibonacci - Darmajid; Dwi Mifta Mahanani (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
Let  be a finite subset of Fibonacci numbers set. In this research, we construct a graph  where the set of vertices contains integer numbers such that for every , there exist some edge  in  that satisfies the condition . By applying some properties of the Fibonacci numbers, we prove that if  contains the first  consecutive Fibonacci numbers then  has the smallest order . Furthermore, we give the sufficient conditions for  become simple graph  and contains no cycle.  Keywords: edge of graph, Fibonacci number, order of graph, simple graph, cycle.